The role of nursing and the impact of nursing research in Europe - Smith, Lorraine N. (Nursing Problems / Problemy Pielęgniarstwa, 2007)
This presentation is part of an international symposium on obesity and reflects specifically on recent changes in nursing research in Europe. The charismatic nursing leaders of the past laid good foundations upon which we can build, yet nursing is often seen as lacking leadership and, as a discipline, is regarded by many as having produced little by way of significant research. Those of us who work in nursing research recognise that there are a number of problems that make the conduct of research difficult for us; these involve structural problems and issues around capacity and capability. Nevertheless, there are grounds for believing that nursing research is growing in maturity and importance as discussed in this paper.